The new media economics of video-on-demand markets: Lessons for competition policy - Oliver Budzinski; Nadine Lindstädt-Dreusicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2018)
The markets for audiovisual content are subject to dynamic change. Where once "traditional" (free-to-air, cable, satellite) television was dominating, i.e. linear audiovisual media services, markets display nowadays strong growth of different types of video-on-demand (VoD), i.e. nonlinear audiovisual media services, including both Paid-for VoD like Amazon Prime and Netflix and Advertised-financed VoD like YouTube. Competition policy decisions in such dynamic markets are always particularly challenging. The German competition authority was presented such a challenge when, at the beginning of the 2010s, German television providers sought to enter online VoD markets with the help of cooperative platforms. We review the antitrust concerns that were raised back then in an ex post analysis. In doing so, we first discuss the dynamic development of the German VoD markets during the last decade. In the second part of this paper, we derive four aspects, in which the previous antitrust analysis cannot be upheld from today's perspective. First, relevant implications of modern platform economics were neglected. Second, some inconsistencies in the assessment of the two projects appear to be inappropriate. Third, the emerging competitive pressure of international VoD providers was strongly underestimated. Fourth, the question of market power in online advertising markets looks very different at the end of the decade.
Keywords: L40; L82; K21; L13; D40; 330; video-on-demand; media economics; two-sided markets; competition; platform economics; commercial television; public service broadcasters; antitrust policy; YouTube; Amazon; Netflix